Fairy tale - "Cowley, Joy" (Hawthorn; Mimosa McGraw-Hill, 2007)
Ross Beansack, the big hairy author, writes stories for modern children about saving whales, the rainforest, and the planet. But when he's visited by an extremely small, green, shrieking person who insists he write about magical creatures, it's enough to make the milk (and his very modern publisher) go sour.
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Fairies Fiction